International, multicenter evaluation of a new D-dimer assay for the exclusion of venous thromboembolism using standard and age-adjusted cut-offs. Issue 166 (June 2018) - Parry, Blair Alden; Chang, Anna Marie; Schellong, Sebastian M.; House, Stacey L.; Fermann, Gregory J.; Deadmon, Erin K.; Giordano, Nicholas J.; Chang, Yuchiao; Cohen, Jason; Robak, Nancy; Singer, Adam J.; Mulrow, Mary; et al.
Abstract: Introduction: We sought to determine the test characteristics of an automated INNOVANCE D-dimer assay for the exclusion of pulmonary embolism (PE) and deep venous thrombosis (DVT) in emergency department (ED) patients using standard and age-adjusted cut-offs. Methods: Cross-sectional, international, multicenter study of consecutive patients with suspected DVT or PE in 24 centers (18 USA, 6 Europe). Evaluated patients had low or intermediate Wells PE or DVT scores. For the standard cut-off, a D-dimer result <500 ng/ml was negative. For the age adjusted cut-off, we used the formula: Age (years) ∗ 10. The diagnostic standard was imaging demonstrating PE or DVT within 3 months. We calculated test characteristics using standard methods. We also explored modifications of the age adjustment multiplier. Results: We included 3837 patients and excluded 251. The mean age of patients evaluated for PE (n = 1834) was 48 ± 16 years, with 676 (37%) male, and 1081 (59%) white. The mean age of evaluated for DVT (n = 1752) was 53 ± 16 years, with 710 (41%) male, and 1172 (67%) white. D-dimer test characteristics for PE were: sensitivity 98.0%, specificity 55.4%, negative predictive value (NPV) 99.8%, positive predictive value (PPV) 11.4%, and for DVT were: sensitivity 92.0%, specificity 44.8%, NPV 98.8%, PPV 10.3%. Age adjustment increased specificity (59.6% [PE], 51.1% [DVT]), but increasing the age-adjustment multiplier decreased sensitivity without increasing specificity. Conclusions: INNOVANCE D-dimer is highly sensitive and can exclude PE and DVT in ED patients with low- and intermediate- pre-test probability. Age-adjustment increases specificity, without increasing false negatives. Highlights: The INNOVANCE D-dimer is highly sensitive; PE and DVT can be excluded by D-Dimer. Age-adjusting D-dimer allows more patients to be safely excluded for PE and DVT. More PE and DVTs are missed as you increase the age-adjustment threshold.